Effect of iron mining tailings as a red ceramic additive for decreased sintering temperature - Amaral,Igor Brumano Coelho (2020)
ABSTRACT The ceramic materials industry includes the burning process at high temperatures in a way that the energy expense of the conventional methods of burning is very high. Using alternative raw materials shows a large potential in this process, such as wastes from other industrial processes, which may reduce the burning temperature of the ceramics, providing desirable characteristics with lower energy expense, as additives that have a high fluxes content, such as iron ore tailings. The waste used had its chemical composition analyzed by X-Ray Fluorescence, mineralogical composition analyzed by X-ray Diffraction and Granulometry by sieving and sedimentation. To study the properties of ceramic test pieces with addition of wastes, we used three different temperatures in the burning process to test if the use of the waste could improve its characteristics. We produced test pieces including a mixture of soil with 10 and 20% content of waste exposed to the sintering process at temperatures of 750, 850 and 950° C. To test the technological properties of the pieces we performed tests of linear shrinkage, loss on fire, coloring, water absorption, apparent porosity, compressive strength and scanning electron microscopy. The color of the test pieces was intensified, and the tested characteristics that showed improvements when the burning temperature decreased. However, at defined concentrations there was little variation in the test pieces produced with pure soil.